R2 Emergency Medicine Multipatient Simulation - Joseph Turner; Jonathan Drew; Joshua Mugele; Taylor Duncan; Rebekah Blickendorf; Dylan Cooper (Association of American Medical Colleges, 2015)
Abstract Introduction Simulation is an excellent tool for emergency medicine (EM) resident education, allowing the resident to manage medically complex and critically ill patients in a safe and controlled environment. The clinical practice of EM involves managing multiple patients of variable acuity simultaneously; studies suggest EM physicians task-switch an average of six times per hour. These multiple-patient scenarios are designed to more accurately reflect EM practice and are intended for R2-level emergency medicine residents. Methods Each scenario includes three individual cases/patients that the emergency medicine resident must manage simultaneously. When planning and running the sessions, trainers should use the scenario flowsheets to move from case to case, and then refer to the subsequent case details for further information about each individual simulated patient. Results A total of 24 emergency medicine and emergency medicine-pediatrics residents participated in the scenarios. After each session, the residents were surveyed about the quality of the sessions, with overwhelmingly positive results. After the pilot session, faculty trainers and simulation technicians were also surveyed. On the survey multiple participants noted the realism and quality of cases, in addition to case complexity, and good flow with attention to multitasking. Discussions The scenarios require significant resources and a large simulation center to implement. For institutions with less resources, alternative strategies can be used such as putting more than one patient in the same room, using halls if space is limited (this simulates actual EM practice), or substituting live human actors if not enough mannequins are available.